Integrating Physics Concepts into Practical Learning through Smart Robot Projects for High School Students in SMAN 3 Pamekasan Madura - Yunata, Ersyzario Edo; Sapuan, Imam; Ukhrowiyah, Nuril; Suaebah, Evi (Department of Physics, Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Surabaya (UNESA), 2025)
This community service program was designed to integrate fundamental physics concepts into practical learning through the implementation of smart robot projects, aiming to enhance students’ comprehension and interest in physics. Conducted at SMAN 3 Pamekasan, Madura, the program involved the design, assembly, and functional testing of four line follower robots and one water-based fire extinguisher robot. Preparatory stages included intensive prototyping and coding trials at the Electronics Laboratory, Department of Physics, Universitas Airlangga, followed by a field survey to the school to assess readiness and requirements. The main activity engaged students in hands-on tasks, encompassing mechanical assembly, electronic circuit integration, and programming, thereby enabling them to directly observe the application of physics principles in robotics. Evaluation using pre-test and post-test instruments indicated a measurable improvement in understanding, with average scores rising from 6.83 to 7.42. These results demonstrate the effectiveness of project-based learning in fostering not only cognitive gains but also positive attitudes toward physics by reframing it as an applied and engaging discipline rather than purely theoretical.